Os isômeros do isopulegol bloqueiam canais para cálcio tipo-l e atenuam a hipertrofia cardíaca em rato: via PKA e ERK 1/2 - Menezes Filho, José Evaldo Rodrigues de (2019)
Introduction: Cardiac hypertrophy (CH) is characterized by the remodeling of cardiac muscle associated with change in its contractile and electrical function. Isopulegol is an alcoholic monoterpene with antioxidant, anxiolytic and anticonvulsant activities. Objectives: To investigate the effects of (+)-isopulegol ((+) - ISP) and (-)-isopulegol ((-)-ISP) isomers on intracellular calcium signaling and cardiac hypertrophy induced by isoproterenol (ISO). Methods: The contractile effects of isomers were evaluated in rat left atrium mounted and ventricular cardiomyocyte of rat by shortening fraction using edge detection system (Ionoptix). In ventricular cardiomyocyte were evaluated the L-type calcium current (ICa,L) by patch-clamp technique in ‘whole-cell’ configuration and intracellular calcium transient by confocal microscopy (FLUO 4AM) was investigated in control situation and after incubation with 100 μM of both isomers. The docking was done to analysis the interaction of isomers with the L-type calcium channel. Cardiac hypertrophy was induced by administration of ISO (4.5 mg/kg, 7 days, i.p.). Four groups of animals were evaluated: 1) control (saline 0.9% + DMSO 0.1%), 2) isoproterenol (ISO), 3) ISO + (-)-ISP (50 mg/kg) and 4) ISO + (+)-ISP (50 mg/kg). In hypertrophic and treated animals were evaluated morphometric and electrocardiographic parameters, biochemical markers (LDH, CPK and CK-MB), oxidative stress (TBARS, SOD, CAT e GPx), inflammatory mediators (TNF-α and IL1-β), expression of proteins (PKA C-α, CAMKII, α/β CAMKII, ERK ½ total, p-ERK ½, SERCA, sarcalumenin, PP1γ e NCX. Results: showed that (-)-ISP (EC50 = 533.0 ± 53.80 μM) and (+)-ISP (EC50 = 1836 ± 165.71 μM) reduced the atrial contractility, of concentration dependent manner. In ventricular cardiomyocytes, after incubation with 100 μM of (-)-ISP and (+)-ISP was observed reduction of shortening fraction (40% and 28%) and ICa,L (68% and 59%), respectively. In addition, (-)-ISP e (+)-ISP reduced the intracellular calcium transient in 21% and 22%, respectively. The docking revealed the interaction of (-)-ISP and (+)-ISP with the L-type calcium channel with energies -65.84 Kcal/mol and -63.09 Kcal/mol. Hypertrophic animals presented increase of heart weight/body weight ratio (5.12 ± 0.09 mg/g, p < 0.05) as well as heart weight/tibia length ratio (364.20 ± 13.74 mg/cm, p < 0.05) in compared to control (3.52 ± 0.11 mg/g; 246.2 ± 6.33 mg/cm) and were attenuated with treatment with (-)-ISP (4.26 ± 0.11 mg/g and 299.40 ± 7.45 mg/cm) and (+)-ISP (4.42 ± 0.03 mg/g and 318.10 ± 3.24 mg/cm). (-)-ISP and (+)-ISPs were able to prevent electrocardiographic changes (increase of QRS, QTc and intrinsicoid deflection) and increase of serum levels of LDH, CPK and CPK-MB of hypertrophic animals. In addition, the treatment of hypertrophic animals with (-)-ISP and (+)-ISP the oxidative promoted decrease of TBARS and increase of SOD, CAT and GPx. Furthermore, inflammatory mediators TNF-α (in 59% and 40%) and IL1-β (in 34% and 55%) were reduced in the two groups treated with (-)-ISP and (+)-ISP, respectively. Treatment of animals with (-)-ISP and (+)-ISP decreased the overexpression of proteins involved in cardiac hypertrophy (PKA, ERK1/2, NCX), as well as prevented the decrease of SERCA and sarcalumelin expression. Conclusion: The isopulegol isomers block L-type calcium channels reducing the intracellular calcium transient in the ventricular cardiomyocyte exhibiting cardioprotective effect in isoproterenol-induced cardiac hypertrophy model